Persepsi Anggota Ekstrakurikuler Bola Basket terhadap Penggunaan Aplikasi Papan Strategi Berbasis Android - MR. Widarto Umbara Pratama; Rizki Yuliandra (Universitas Teknokrat Indonesia, 2021)
Research on the perception of the member of extracurricular SMA N 7 Bandar Lampung from the use of android-based strategy board applications was descriptive research. The purpose to be achieved in this study was to determine Android Member Perception Basketball of SMA N 7 Bandar Lampung against the Use of Android Based Strategy Board. This study used a qualitative approach with the data analysis of the questionnaire to the object. The population in this study was participants extracting basketball extract SMAN 7 Bandar Lampung, which amounted to 30 people. Based on the results, it showed that the participants had an agreeing perception of the use of the 2021 strategy board app. The results of this study are a reference for coaches to be able to provide exercises that vary through the help of using android-based strategy board and not.